Reducing NAFLD‐screening time: A comparative study of eight diagnostic methods offering an alternative to ultrasound scans. (22nd October 2018) - Procino, Filippo; Misciagna, Giovanni; Veronese, Nicola; Caruso, Maria G.; Chiloiro, Marisa; Cisternino, Anna M.; Notarnicola, Maria; Bonfiglio, Caterina; Bruno, Irene; Buongiorno, Claudia; Campanella, Angelo; Deflorio, Valentina; et al.
Abstract: Background & Aims: The use of ultrasound scan (US) in non‐alcoholic fatty liver disease (NAFLD) screening overloads US waiting lists. We hypothesized and tested a hybrid two‐step method, consisting of applying a formula, to exclude subjects at low risk, before US. Methods: The sample included 2970 males and females (937 with NAFLD) diagnosed by US. We selected eight formulas: Fatty Liver Index (FLI), Hepatic Steatosis Index (HIS), body mass index (BMI), waist circumference (WC), Abdominal Volume Index (AVI), waist‐to‐height ratio (WHtR), waist/height 0.5 (WHT.5R) and Body Roundness Index (BRI), and calculated their performance in the two‐step method evaluating percentage reduction of the number of liver US (US reduction percentage), percentage of false negative and percentage of NAFLD identified. Results: The US reductions percentage were 52.2% (WHtR), 52.1% (HIS), 51.8% (FLI), 50.8% (BRI), 50.7% (BMI and WHt_5R), 46.5% (WC) and 45.2% (AVI). The false negative percentage were 8.5% (WHtR), 7.9% (BRI), 7.3% (WHt_5R), 7.2% (BMI), 6.7% (HIS), 6.6% (FLI), 5.6% (WC) and 5.2% (AVI). The best percentage of NALFD identified was obtained using AVI (83.6%) before US, then WC (82.2%), FLI (79%), HIS (78.9%), BMI (77.3%), WHt_5R (76.9%), BRI (74.8%) and WHtR (73%). Conclusion: The best formula to use in two‐step diagnostic NAFLD screening was AVI, which showed a low false negative rate and a higher percentage of identified NAFLD. Other studies evaluating the economic advantages of this screening method are warranted.